Language skills level among students with mental disabilities at Ajloun Governorate - Wahsheh, Nayef Ali (Nurture, 2023)
Purpose: To define the level of language skills among students with mental disabilities. Design/Methodology/Approach: The population and the sample (n = 106) included students with mild and moderate mental disabilities enrolled in special education centres at Ajloun Governorate. The descriptive analytical design was used using a questionnaire consisting of (32) items. Findings: The level of language skills among students with mental disabilities was low. Statistically significant differences were found in light of the disability’s degree in all domains and the total score in favour of moderate mental disabilities, while no statistically significant differences were found in light of gender. Conclusion: The language skills topic for students with mental disabilities is one of the most important topics among specialists in special education. Thus, the primary issue with this research revolves around the level of language skills among students with mental disabilities at Ajloun governorate. The study found that the mean score for the level of language skills among students with mental disabilities was 0.37, with a low level. So, it is recommended to concentrate the efforts of educators, parents, and officials to increase the interest in this group of students, and to provide all material, moral, and training means to develop their social skills in order to become better. Practical Implications: The importance of this study stems from the fact that it sheds light on the level of language skills among students with mental disabilities, which in turn will affect the process of providing different programs for students with mental disabilities, especially those related to developing their language skills. The study complements the previous researchers’ work on the language skills of students with mental disabilities; it could be a starting point to address the topic from other aspects and with multiple variables.